The impact of community empowerment programs on achieving sustainable development goals in local communities - Mohd Zahari, Haliza; Ridwan Wong, Mohd Muhaimin; Abas, Fuad; Fazann Ahmad, Noor Diyana; Shukor, Nurul Naqirah; Wan Hussein, Wan Nurhasniah (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2025)
The government in any country holds responsibility for the governance and administration. However, to enable the successful implementation of all policies at the local level, the government requires a mechanism that aligns with its objectives. Hence, civil society has a crucial role in assisting the government in disseminating precise information and executing initiatives for the community. The objectives of this study are to identify the activities executed under the MyICE Grant and assess their potential impact on the community, in accordance with the objectives of the Sustainable Development Goals (SDG). This study has utilized two methodologies, specifically Focus Group Discussion (FGD) and interview. A total of 15 Focus Group Discussion (FGD) sessions were conducted, consisting of 214 participants from diverse groups who had successfully obtained MyICE grants from the Registrar of Society, Malaysia. There are a total of 124 community empowerment programs that have been mapped with the SDG. It was noted that the programs are designed specifically for the local community and have potential to contribute to the achievement of the SDG. These programs enable the effective implementation of government initiatives aimed at improving community well-being. Collaboration with other government agencies and organizations to deliver community programs is crucial to improving information transmission and community awareness through increased involvement. However, due to the program being executed as one-off activities, the effectiveness of the program's was not conclusive. Therefore, research on community program achievements should be conducted to assess the impact of the implemented program. This evaluation should not only focus on the successful implementation of the program but also consider the program's output and outcome.